Multiple Subsonic Jet System in the Presence of Cross Flow - Hendrikson, V. (Engineering Transactions, 1976)
The series of three parallel subsonic turbulent jets issuing from circular nozzles into the cross flow was studied experimentally, Main characteristics of flow: were found to be functions of the ratio of jet to stream momentum, the distance between the nozzles and the mode of orientation of series. Results of study at various flow conditions are presented.